Board Capital, Corporate Social Responsibility Disclosure Quality, And Firm Performance In Saudi Arabia: Does Ceo Power Matter? - Maswadi, Laila Ali M (2023)
The current trend in corporate social responsibility research has shifted to the reporting quality of organizations. With the trend shifting in CSR literature toward the quantity and quality of corporate social responsibility disclosure, this research endeavors to use Agency Theory and Resource Dependence Theory to investigate the relationship between board capital (human and social capital) and corporate social responsibility (CSR) disclosure quality in the Saudi non-financial firms. It further investigates the relationship between corporate social responsibility disclosure quality and firm performance. Additionally, this research examines the moderating role of CEO power on the relationship between board capital and CSR disclosure quality. Given that influence of board capital is relatively low in Saudi firms, powerful CEOs seek to improve and sustain CSR disclosure quality.